The Integration Of Artificial Intelligence In English Language Teaching And Machine Translation: A Bridge Between Theory And Practice In Language Teaching For Specific Purposes. - Hafida Slimani; Rachid Saim (The Journal of Studies in Language, Culture and Society)
Integrating AI into ELT and machine translation marks a major advancement, particularly in the teaching of languages for specific purposes (LSP). This field is crucial in a globalized context, where proficiency in foreign languages and specialized communication is essential. This study explores how AI can serve as a bridge between theory and practice by analyzing tools such as neural machine translation systems (DeepL, Google Translate), pedagogical assistants (ChatGPT), and case studies in specialized educational contexts (medicine and engineering). The findings revealed that AI enables greater personalization of learning, optimization of educational resources, and facilitation of intercultural communication. However, it also raises challenges, such as the reliability of machine translations, algorithmic biases, and excessive dependence on technology. In conclusion, AI offers transformative opportunities for ELT and LSP, but its integration requires a balanced approach, critical teacher training, data protection, and focus on educational equity. Future perspectives include adaptation to underrepresented languages and a study of its long-term impact.